ANALISIS SOAL TES BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA BILANGAN CACAH KELAS IV DI SD NEGERI 104218 SIDOMULYO - Panjaitan, Riza Wita; Nurjannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this research was to determine the validity, reliability, difficulty level, discriminating power, and distractor effectiveness of 15 multiple-choice mathematics questions on whole numbers for Grade IV students at SDN 104218 Sidomulyo. This research employed a quantitative descriptive method. The population consisted of 42 students, while the sample included 23 students. The research instrument was a set of 15 multiple-choice mathematics questions on whole numbers for Grade IV. Data analysis was conducted using SPSS Software and Microsoft Excel. The research findings indicate that 5 questions (33.3%) were valid, while 10 questions (66.7%) were invalid. The test instrument scored < 0.6, making it unreliable. All 15 questions had a moderate difficulty level. The discriminating power of the test items varied, with 4 questions classified as very poor, 6 questions as poor, 3 questions as fair, and 2 questions as good. Regarding the effectiveness of the distractors, only a few items required revision, and only one option was rejected or replaced.